The Elasticity of Perception: Undermining the (Non-)Conceptualism Debate - Endres, Tobias (Studia Kantiana, 2023)
In the current philosophy of perception, a debate about whether concepts permeate perceptual states in constituting the perceptual object or not has been widely discussed. Analytic philosophers and phenomenologists participate in this debate likewise, but it is also a debate in Kantian scholarship since the conceptualists’ thesis goes back to Kant’s Criticism and neo-Kantians already discussing such theory against any philosophy of immediate experience long before Wilfrid Sellars had started his attack against the so-called myth of the given. In light of this historical panorama, the article reconstructs Ernst Cassirer’s views on perception in order to systematically reject both Conceptualism and Non-Conceptualism. It can be shown that both positions are uncritical stances which make claims to either the absoluteness of language or perception and that much-discussed arguments such as the fineness of grain argument rely on a category mistake. The proposed solution is a view that upholds the criticism against the myth of the given, but replaces the idea of a conceptual mediation of perceptual experience with a symbolic mediation. As a consequence, perception must perform a paradoxical feat and has thus to be elastic.